Impact of residual platelet reactivity on reperfusion in patients with ST-segment elevation myocardial infarction undergoing primary percutaneous coronary intervention. Issue 5 (September 2016) - Capranzano, Piera; Capodanno, Davide; Bucciarelli-Ducci, Chiara; Gargiulo, Giuseppe; Tamburino, Claudia; Francaviglia, Bruno; Ohno, Yohei; La Manna, Alessio; Antonella, Salemi; Attizzani, Guilherme F; Angiolillo, Dominick J; Tamburino, Corrado
Aim: Whether high platelet reactivity (HPR) immediately after diagnostic angiography is associated with worse coronary reperfusion prior to and after primary percutaneous coronary intervention (PPCI) for ST-segment elevation myocardial infarction (STEMI) is unknown. This study aimed to assess the impact of P2Y12 -mediated HPR on angiographic outcomes in patients with STEMI undergoing PPCI. Methods: STEMI patients undergoing PPCI and pretreated with a P2Y12 receptor antagonist underwent platelet function testing with the VerifyNow™ assay at the time of angiography. Light transmission aggregometry (LTA) was performed in a subgroup. HPR was defined according to expert consensus definitions. Pre-PCI coronary patency, thrombotic burden and indices of impaired post-PCI reperfusion were compared between HPR and non-HPR patients. Results: Among 164 patients, the prevalence of VerifyNow™-derived HPR was 71.3% at a median (interquartile range (IQR)) of 55 (40–75) minutes after a P2Y12 inhibitor loading dose. Compared with non-HPR patients, those with HPR had significantly lower rates of pre-PCI Thrombolysis in Myocardial Infarction (TIMI) flow grades 2 or 3 (51.1% vs. 32.5%, p  = 0.04), higher rates of thrombus score (TS) grade 3/4 (29.8% vs. 52.1%, p  = 0.015) and 4 (14.9% vs. 32.5%, p  = 0.037) and lower median (IQR) corrected TIMI frame count (cTFC; 23.2 (15.8–32.5) vs. 26.0 (21.0–35.0), p  = 0.02), respectively. These findings were consistent using LTA-based data. HPR and TS grade 4 were predictors of higher cTFC. Conclusions: In patients with STEMI undergoing PPCI pretreated with P2Y12 receptor inhibitors, pre-PPCI HPR was found to be associated with lower pre-PCI coronary patency, higher thrombotic burden and a worse index of post-PCI coronary reperfusion.